If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8v + -34 = 7(v + -7) Reorder the terms: -34 + -8v = 7(v + -7) Reorder the terms: -34 + -8v = 7(-7 + v) -34 + -8v = (-7 * 7 + v * 7) -34 + -8v = (-49 + 7v) Solving -34 + -8v = -49 + 7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-7v' to each side of the equation. -34 + -8v + -7v = -49 + 7v + -7v Combine like terms: -8v + -7v = -15v -34 + -15v = -49 + 7v + -7v Combine like terms: 7v + -7v = 0 -34 + -15v = -49 + 0 -34 + -15v = -49 Add '34' to each side of the equation. -34 + 34 + -15v = -49 + 34 Combine like terms: -34 + 34 = 0 0 + -15v = -49 + 34 -15v = -49 + 34 Combine like terms: -49 + 34 = -15 -15v = -15 Divide each side by '-15'. v = 1 Simplifying v = 1
| 8(u+8)=3u+14 | | 7x^2-6x=-1 | | (5x+62)(3x+47)37=180 | | 4=x-7x-8 | | 7(c-7)=6(3+c) | | 1/3(18-6x)=8-3x | | 1/3(18x-6x)=8-3x | | 2=9+w | | -2y+180=x | | 144a^2+b^2-24ab=0 | | 14+2=-2(6y-8) | | -y-3=-9 | | 3(2x+9)=-37+46 | | 3[6+(-2)]= | | b-81b^3=0 | | T(2)-10t=39 | | 2t^4-3= | | 6x-7=5(x-1)+(x-2) | | x^2+6x+9-64=0 | | X(-2)-8=0 | | -x+3+2z=0 | | X-2-8=0 | | 1/4Y-1/2Y=1/6 | | 6x-7=5(x-1)+(x+2) | | 2x^2-4x-4=2 | | (9w-2)(7w-3)=0 | | 8x-28+3x+4=108 | | Lnx=1+3lnx | | 1/4Y-1/2Y | | 4-7=-27 | | s^2-2sy-63y^2= | | (2y+3)(y-9)=0 |